Aryl Hydrocarbon Receptor Mechanisms Affecting Chronic Kidney Disease - Curran, Colleen S.; Kopp, Jeffrey B. (Frontiers in Pharmacology, 2022)
The aryl hydrocarbon receptor (AHR) is a basic helix-loop-helix transcription factor that binds diverse endogenous and xenobiotic ligands, which regulate AHR stability, transcriptional activity, and cell signaling. AHR activity is strongly implicated throughout the course of chronic kidney disease (CKD). Many diverse organic molecules bind and activate AHR and these ligands are reported to either promote glomerular and tubular damage or protect against kidney injury. AHR crosstalk with estrogen, peroxisome proliferator-activated receptor-γ, and NF-κB pathways may contribute to the diversity of AHR responses during the various forms and stages of CKD. The roles of AHR in kidney fibrosis, metabolism and the renin angiotensin system are described to offer insight into CKD pathogenesis and therapies.